(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses the importance of mastering English in the modern, interconnected world and offers practical strategies to help individuals achieve proficiency in the language. It emphasizes English’s crucial role in personal and professional success, as it is the primary language for global communication, business, and academia. The article outlines several effective approaches for mastering English, including immersive learning, daily practice, expanding vocabulary and grammar, setting achievable goals, and utilizing technology and language learning tools.